LANDASAN PSIKOPEDAGOGIS KURIKULUM CINTA DALAM MEMBANGUN PEMBELAJARAN HOLISTIK DI SEKOLAH DASAR - Naila Ainun; Lu’luil Maknun (As-Sulthan Journal of Education, 2026)
This study aims to examine how a psychopedagogical foundation can support the implementation of the Love Curriculum in realizing holistic learning at the primary school level. The Love Curriculum emphasizes love, empathy, and appreciation for students’ comprehensive development, including cognitive, social, and emotional aspects. This research uses a literature review method, systematically analyzing relevant sources on child developmental psychology, humanistic pedagogy, and holistic learning theory. The findings show that a deep understanding of child development psychology is essential for educators to apply a loving and responsive teaching approach. The Love Curriculum fosters a supportive learning environment that promotes optimal character development and emotional balance. Additionally, it successfully integrates academic and affective elements into a unified holistic learning process. Although this study is conceptual and has not yet been empirically tested, it offers a novel perspective by integrating psychopedagogical principles with the values of love in primary education curriculum development. These findings contribute significantly to curriculum design and enhancing educators’ capacity to provide a more humanistic and comprehensive educational experience.